DAMPAK TEKNOLOGI DIGITAL TERHADAP PEWARTAAN INJIL DALAM KONTEKS MENGGEREJA - Yeremia Hia; Elfin Warnius Waruwu (Phronesis: Jurnal Teologi dan Misi, 2023)
The development of digital technology has provided new opportunities and challenges in efforts to proclaim the Gospel. Through social media, websites, and other online platforms, evangelizers can reach a wider audience and communicate directly with individuals or groups. However, not all evangelizers or churches can utilize technology effectively to get new souls into evangelism. In this research, the author uses a qualitative approach, which cannot be separated from observation methods and literature studies, to support comprehensive and valid data. To make good use of the potential of digital technology, this article invites churches and Christian missionaries to continue learning, adapting, and using digital tools in ways that support evangelists' vision. By holistically understanding and using digital technology's impact wisely, churches can strengthen their evangelisation efforts and present the Christian message to an increasingly digitally connected generation.